Blending efficiency improvement and energy investigation of recycled asphalt mixture involved warm mix technology. (10th January 2021) - Hou, Xiangdao; Hettiarachchi, Chamod; Xiao, Feipeng; Zhao, Zifeng; Xiang, Qian; Yong, Dara
Abstract: The application of reclaimed asphalt pavement (RAP) materials has become an important subject of sustainable development in the field of road construction. In addition, the low carbon asphalt technology (i.e. warm mix technology) is recently employed to reduce the energy consumption and emission in RAP application. Generally, during the RAP mixing process, softer asphalt or rejuvenator is typically used to offset the aged effect of RAP materials. Therefore, further investigation on blending efficiency of virgin and aged asphalts in terms of warm mix technology and its influence factors has become extremely important to save the energy and reduce the emission. In this study, Fourier Transform Infrared Spectroscopy was used to evaluate the blending degree of virgin and aged asphalts involved warm mix additive. Additionally, some factors such as blending time, blending temperature, and RAP content on the blending efficiency were investigated in the study. The research results indicated that all these factors had individual or combined effects on the blending degree of recycled asphalt mixtures. Furthermore, the energy consumption of mixing process was measured based on a laboratory study. It was found that an extended blending duration had a better energy effectiveness on increasing the blending degree within the first 3-min. After that, the blending degree could be improved efficiently with less energy consumption by increasing the blending temperature. In addition, utilizing warm mix additive could also significantly promote blending efficiency.